Zoonotic hepatic helminths and their histopathological characterization in Rattus spp from a zoo, pig farm and food markets - Chuquillanqui Trujillo, Gustavo (2022)
The study aimed to determine the prevalence of zoonotic liver helminths and their histopathological characterization in rodents (Rattus spp.) from a zoo, pig farms and food markets in Lima, Perú. The morphometric parameters of each rodent were recorded to determine the age and identify the species, computing a total of 267 animals. The handling and the capture methodology were carried out according to the biosafety standards established by the Center for Infectious Diseases and Prevention of Atlanta. Livers were macroscopically evaluated for lesions. For diagnostic confirmation by histopathology, samples were taken from the right lateral lobe of all the livers together with other areas that showed damage in search of tissue lesions and inflammatory response related to the presence of the parasites. The pathological analysis determined a prevalence of 3.74% of Cysticercus fasciolaris in Rattus spp. without finding Capillaria hepatica. Statistical analysis did not show a statistically significant association between the study variables and C. fasciolaris. The most common histopathological diagnosis was moderate to severe granulomatous eosinophilic cholangiohepatitis associated with C. fasciolaris. The results indicate that rats can be sources of C. fasciolaris infections in various environmental settings, therefore, they allow us to understand the health risk of the zoonoses they transmit and their management.